PUBLIC PERCEPTIONS OF GENDER STEREOTYPES AND SOCIAL ACCEPTANCE TOWARD SEXUAL ORIENTATION AMONG WOMEN FOOTBALL ATHLETES IN WEST JAVA - Zahra Naqiyyah Primadi; Surdiniaty Ugelta; Unun Umaran (Kafa`ah: Journal of Gender Studies, 2026)
This study examines public perceptions of gender stereotypes and social acceptance of sexual orientation in women’s football in West Java, Indonesia. Despite the global growth of women’s football, female athletes continue to face social judgments that extend beyond athletic performance, particularly related to gender expression and assumed sexual orientation. Adopting a qualitative descriptive design grounded in the social constructionist perspective, this study collected data through semi-structured interviews and non-participant observation. Participants were selected using purposive sampling from four social groups: the general public, religious backgrounds, educational sectors, and local cultural or community groups. Data were analyzed using directed thematic analysis combining inductive and deductive strategies. The analysis identified a central theme: the social construction of gender stereotypes and conditional social acceptance toward the sexual orientation of female footballers. Findings show that female footballers are commonly stereotyped as masculine and insufficiently feminine, with judgments focused on bodies, appearance, and domestic role expectations. These stereotypes shape public assumptions about sexual orientation, where non-normative gender expressions are often interpreted as indicators of non-heteronormativity. Social acceptance emerges as conditional, influenced by religious beliefs, cultural norms, educational exposure, and social environments. Acceptance is generally granted when athletes conform to dominant gender norms and limit the public visibility of personal identity. This study highlights how gender stereotypes and conditional acceptance function as interconnected social mechanisms regulating legitimacy and belonging in women’s football